Kacip Fatimah (Labisia pumila) as Natural Sunscreen: Analysis of Flavonoid Content and Ultraviolet Protection Ability - Rahmatullah, Satrio Wibowo; Rizki, Muhammad Ikhwan; Sari, Anna Khumaira; Sari, Fitri Novita; Fadlilaturrahmah, Fadlilaturrahmah; Junjung Buih, Putri Helena (Tropical Health and Medical Research, 2025)
The cause of melanoma cancer is exposure to high-intensity ultraviolet rays from sunlight. Kacip Fatimah (Labisia pumila) utilizes the people of the interior of Kalimantan to protect their skin from sunlight by attaching leaves to the face or skin. Kacip Fatimah (Labisia pumila) contains flavonoid compounds, which are thought to impact these various properties. This study aimed to determine the ultraviolet protection ability and total flavonoid levels of Kacip Fatimah (Labisia pumila) leaves. Kacip Fatimah (Labisia pumila) leaves originating from Central Kalimantan were cleaned, dried in an oven, ground, and then extracted with air solvents, 70% ethanol, and 96% ethanol. Flavonoid identification was carried out with specific reagents, and total flavonoid levels were determined by colorimetric method using quercetin as a comparison. The ultraviolet protection ability of Kacip Fatimah (Labisia pumila) leaf extract was measured using a UV-Vis Spectrophotometer with the Sun Protection Factor parameter. The results showed the presence of flavonoids in the third extract. The total flavonoid content of air extract, ethanol 70%, and ethanol 96% from Kacip Fatimah (Labisia pumila) leaves were obtained respectively at 1.69%, 2.15%, and 2.38%. The most extracted flavonoids were in ethanol 96%solvent. The ultraviolet protection ability at a concentration of 100 - 500 ppm from air extract was in the range of 2.80 - 7.99, in ethanol 70% extract in the range of 5.69 - 38.39, while in ethanol 96% extract in the range of 8.76 - 49.07. The highest ultraviolet protection was in 96% ethanol extract from Kacip Fatimah (Labisia pumila) leaves. The results showed that Kacip Fatimah (Labisia pumila) leaves can provide ultraviolet protection with the content of active compounds of the flavonoid group. The research results can be scientific evidence for utilizing and developing products from Kacip Fatimah (Labisia pumila).